The Benefits of Holistic Therapy for Psychological Disorders in Postpartum Mother: A Systematic Review - Syafrida Ainur; Lucky Herawati; Melyana Nurul Widyawati (Universitas STRADA Indonesia, 2020)
Physical and psychological changes during postpartum period can make postpartum mother vulnerable to psychological disorders such as anxiety and depression. The purpose of this study was to identify and analyze several holistic therapies that are beneficial for reducing psychological disorders during postpartum period. The inclusion criteria in this study were articles in english; samples in the form of postpartum mothers; and experimental research. There are 12 research articles that included in the analysis of this research, research articles on mindfulness (n = 4), massage (n = 4), and aromatherapy (n = 4). Holistic therapy can affect the regulation of the nervous system and reduce levels of cortisol hormone. Holistic therapies such as mindfulness, massage, and aromatherapy have been shown to be beneficial for reducing psychological disorders such as anxiety to depression in postpartum mothers which have an impact on increased relaxation and positive mood.